Mark's gospel: history, theology, interpretation - Black, C. Clifton (Wm. B. Eerdmans Publishing Co., 2023)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Tables -- Preface -- List of Abbreviations -- Introduction: A Brief Commentary on the Gospel According to Mark -- Part One: Historical Studies -- 1. Was Mark a Roman Gospel? -- 2. The Second Evangelist: Authorship and Apostolicity -- 3. The Quest of Mark the Redactor: Why Has It Been Pursued, and What Has It Taught Us? -- 4. Thirty Years On: Mark's Disciples and Markan Redaction -- 5. A Servant of Surprise: Juel Interpreted -- 6. Markan Studies: Whence and Whither? -- Part Two: Theological Studies -- 7. A Conspectus of Markan Theology -- 8. Mark as Historian of God's Kingdom -- 9. The Face Is Familiar-I Just Can't Place It -- 10. Does Suffering Possess Educational Value in Mark's Gospel? -- 11. Mark: John's Photographic Negative -- 12. Christ Crucified in Paul and in Mark -- 13. Endzeit als Urzeit: Mark and Creation Theology -- 14. An Oration at Olivet -- 15. The Kijé Effect: Revenants in the Markan Passion Narrative -- Part Three: Homiletical Studies -- 16. Priming the Pump: Exegetical Studies for Preachers -- 17. Ministry in Mystery: One Evangelist's Vision -- Acknowledgments -- Bibliography.